Development Tolerance in Early Childhood: Management and Practices for Emancipatory Curriculum - Jumiatmoko; Siti Wahyuningsih; Upik Elok Endang Rasmani; Bambang Winarji; Anjar Fitrianingtyas; Nurul Shofiatin Zuhro; Novita Eka Nurjanah (Universitas Pendidikan Ganesha, 2024)
Tolerance is key to realizing ECEfS (Early Childhood Education for Sustainability). However, the implementation of the Merdeka Curriculum presents new challenges in developing tolerance in early childhood education, particularly due to differences in children's socio-cultural backgrounds and limited variety of stimulating activities.This study aims to identify the dynamics of tolerance development management in PAUD institutions implementing the Kurikulum Merdeka. The research employs a Case Study method, which is suitable for answering